Eyeblink classical conditioning. - Woodruff-Pak, Diana S., 1946-; Steinmetz, Joseph E., 1955- (Kluwer Academic, 2002)
Classical conditioning of the nictitating membrane (NM) eyeblink response in rabbits is a useful model system for the study of the neurobiology of learning and memory. This paradigm that is so well described on a biological level has also been applied to studies of normal development over the life span and to instances of abnormal developmental phenomena. Eyeblink conditioning has been studied from molecular and neural network perspectives, and the paradigm is of demonstrated utility in elucidating mechanisms in physiology and pharmacology. This model system provides a behavioral paradigm in animals that has a close analog in human behavior. Perspectives of recent developments in human eyeblink classical conditioning research are presented in the companion volume to this book, Eyeblink Classical Conditioning: Applications in Humans.